Convergent Evolution of Unique Morphological Adaptations to a Subterranean Environment in Cave Millipedes (Diplopoda). - Weixin Liu; Sergei Golovatch; Thomas Wesener; Mingyi Tian (PLoS ONE)
Animal life in caves has fascinated researchers and the public alike because of the unusual and sometimes bizarre morphological adaptations observed in numerous troglobitic species. Despite their worldwide diversity, the adaptations of cave millipedes (Diplopoda) to a troglobitic lifestyle have rarely been examined. In this study, morphological characters were analyzed in species belonging to four different orders (Glomerida, Polydesmida, Chordeumatida, and Spirostreptida) and six different families (Glomeridae, Paradoxosomatidae, Polydesmidae, Haplodesmidae, Megalotylidae, and Cambalopsidae) that represent the taxonomic diversity of class Diplopoda. We focused on the recently discovered millipede fauna of caves in southern China. Thirty different characters were used to compare cave troglobites and epigean species within the same genera. A character matrix was created to analyze convergent evolution of cave adaptations. Males and females were analyzed independently to examine sex differences in cave adaptations. While 10 characters only occurred in a few phylogenetic groups, 20 characters were scored for in all families. Of these, four characters were discovered to have evolved convergently in all troglobitic millipedes. The characters that represented potential morphological cave adaptations in troglobitic species were: (1) a longer body; (2) a lighter body color; (3) elongation of the femora; and (4) elongation of the tarsi of walking legs. Surprisingly, female, but not male, antennae were more elongated in troglobites than in epigean species. Our study clearly shows that morphological adaptations have evolved convergently in different, unrelated millipede orders and families, most likely as a direct adaptation to cave life.